Impact of center pivot irrigation on vegetation dynamics in a farming-pastoral ecotone of Northern China: A case study in Ulanqab, Inner Mongolia. (June 2019) - Chen, Xin; Wang, Fangtian; Jiang, Li; Huang, Can; An, Pingli; Pan, Zhihua
Graphical abstract: Highlights: The number of center pivot irrigation (CPI) in Ulanqab first increased and then decreased during 2002–2017. Both the average NDVI and the percentage of significant improvement inside the CPI are large than those outside the CPI. Center pivot irrigation caused vegetation degradation within 10, 000 m surrounding the CPIs. There is a significant positive correlation between the size of CPIs and the degree of vegetation degradation. Abstract: Center pivot irrigation (CPI) has expanded rapidly in recent years due to drought in the Farming-Pastoral Ecotone of Northern China (FPENC). However, it is worth questioning whether the promotion of CPI will have adverse effects on highly vulnerable regions. Therefore, we quantify the CPI change patterns in FPENC and its vegetation cover response using trend analysis and spatial correlation methods in conjunction with Landsat images and MODIS data from 2000 to 2017. CPIs in Ulanqab are mainly distributed in the Houshan area, which is characterized by poor hydrothermal conditions. Policy orientation led to obvious phased characteristics of CPI, showing first an increasing trend from 2002 to 2015 and then a sharply decreasing trend by nearly 32.02% from 2015 to 2017. It is not sustainable to vigorously popularize CPI aimed at improving the agricultural production conditions in the Farming-Pastoral Ecotone of Northern China. During the growing season, the expansion of CPI will aggravate the degree of water stress in the area, causing vegetation degradation within 10, 000 m surrounding the CPIs and "pseudo-improvement" of the vegetation inside the CPIs. In the 0–10, 000 m buffer range, the correlation coefficient between the kernel density of CPI buffer pixels (CBKDE) and the kernel density of significantly degraded pixels (DPKDE) was largest in spring (0.243), followed by autumn (0.231) and summer (0.227). Furthermore, the degree of vegetation degradation was positively correlated with the size of CPIs, with correlation coefficients of 0.233 (Rlarge ), 0.167 (Rmedium ) and 0.144 (Rsmall ), respectively. These results can provide a strong basis for decision-making in formulating sustainable agricultural development strategies.